Almost periodic solutions of impulsive integro‐differential neural networks - Stamov, Gani Tr.; Alzabut, Jehad O. (Mathematical Modelling and Analysis, 2010)
In this paper, sufficient conditions are established for the existence of almost periodic solutions for system of impulsive integro‐differential neural networks. Our approach is based on the estimation of the Cauchy matrix of linear impulsive differential equations. We shall employ the contraction mapping principle as well as Gronwall‐Bellman’s inequality to prove our main result. The research of Gani Tr. Stamov is partially supported by the Grand 100ni087–16 from Technical University–Sofia First published online: 10 Feb 2011